Math, asked by kanishkacreat123, 11 months ago

Please ans my question

Attachments:

Answers

Answered by SillySam
6

  \sf \: \frac{ \sqrt{2} +  \sqrt{3}  }{ \sqrt{2}  -  \sqrt{3} }  -  \frac{ \sqrt{2} -  \sqrt{3}  }{ \sqrt{2} -  \sqrt{3}  }  = a - b \sqrt{2}

Rationalising the first term of L.H.S

For rationalising any term , we multiply the term with another term that has the same digits in numerator and denominator both but with the sign opposite to that of the denominator of first term .

 \sf \frac{ \sqrt{2} +  \sqrt{3}  }{ \sqrt{2}  -  \sqrt{3} }  =  \frac{ \sqrt{2}  +  \sqrt{3} }{ \sqrt{2} -  \sqrt{3}  }  \times  \frac{ \sqrt{2} +  \sqrt{3}  }{ \sqrt{2} +  \sqrt{3}  }

 =  \frac{ (\sqrt{2}  +  \sqrt{3}) {}^{2}   }{  { \sqrt{2} }^{2}  -  \sqrt{3} {}^{2} }

 =   \frac{{ \sqrt{2} }^{2} +  { \sqrt{3} }^{2}  + 2 \times  \sqrt{2} \times  \sqrt{3}  } {2 - 3}

 =  \frac{2 + 3 + 2 \sqrt{6} }{ - 1}

 =  \frac{5 + 2 \sqrt{6} }{ - 1}

 =  - 5 - 2 \sqrt{6}

Similarly , Rationalising the second term

   \frac{ \sqrt{2} -  \sqrt{3}  }{ \sqrt{2}  -  \sqrt{3} }  =  \frac{ \sqrt{2}  -  \sqrt{3} }{ \sqrt{2}  -  \sqrt{3} }  \times  \frac{ \sqrt{2}  +  \sqrt{3} }{ \sqrt{2}  +  \sqrt{3} }

 =  \frac{ \sqrt{2}  {}^{2} -  { \sqrt{3} }^{2}  }{ { \sqrt{2} }^{2} -  { \sqrt{3} }^{2}  }

 =  \frac{ - 1}{ - 1}

 = 1

Solving the LHS

 \sf - 5 - 2 \sqrt{6}  - 1 = a  -  b \sqrt{2}

\sf -6 -2 \sqrt{6} = a - b \sqrt{2}

Comparing the coefficients ,

a = -6 and b = 2√3

Answered by ishu2810
1

Answer:

hope it helps u.......

thank u....

Attachments:
Similar questions